Medicine and philosophy: philosophical addressing of some problems of today’s medicine - Peña, Adolfo (2004)
The medical thought and practice pose a number of philosophical problems; these include the characterization of medicine itself, and the epistemological, ethical and logic problems. This essay will philosophically address six current medical problems: The biomedical investigation -evolution today and the implication of the scientific development policies-; the evidence based medicine -its characterization as new paradigm, and the analysis of its “real” role in medical practice-; the characterization of medicine as knowledge and practice -What do we understand by medicine, art, science or technology?-; the problem of lack of a general disease concept -the personal epistemology and its implications in the physicians’ work-; finally, the philosophical examination on the validity of so named alternative medicine. This essay intends to show that the philosophical addressing of many medical problems does not represent a mere intellectual game, but an effective tool for medical research and teaching, mainly, for the critical observation of problems. We intend to show, furthermore, that the philosophy of medicine cannot be summarized only to the ethical and historical plot.